Meningkatkan Motivasi dan Hasil Belajar Peserta Didik dengan Mengoptimalkan Penerapan Model Discovery Learning di SD Negeri 2 Cakranegara - Baiq Nurmiati (Universitas Pendidikan Mandalika, 2019)
The purpose of this study was to determine the effectiveness of the application of the Discovery Learning model in an effort to improve motivation and learning outcomes of grade VI students of SD Negeri 2 Cakranegara. This research method uses classroom action research. This research was conducted in two cycles, each cycle of activities is; planning, implementation, observation and reflection. The final results of the action in the second cycle showed that the observations of teachers at the second meeting obtained an average score (4.57) and the results of observations of the students of the second meeting reached an average score (4.35). While student learning outcomes reach an average value (90.46), meaning that indicators of success (> 4.0) and learning outcomes (> 75.00) have been exceeded. Because the indicators of success have been proven, the research was declared successful and stopped in the second cycle.